Orientalism Reconsidered: Turkey in Barbara Frischmuth's Das Verschwinden des Schattens in der Sonne and Hanne Mede-Flock's Im Schatten der Mondsichel - Petra Fachinger (Studies in 20th & 21st Century Literature, 1999)
Recent German criticism has demonstrated that the relationships of Austria and Germany with the "Orient" have been more complex than Edward Said's Orientalism makes it appear. Furthermore, Said only touches upon gender issues. Studies like Rana Kabbani's Europe's Myths of Orient: Devise and Rule explore the convergence of race, class, and gender in the conceptualization of the "Orient." Kabbani claims that in Elias Canetti's Die Stimmen von Marrakesch the narrator's identification with the colonizer's position enters into his representation of self as much as does his gender. My essay demonstrates how the Austrian writer Barbara Frischmuth and the German writer Hanne Mede-Flock represent their female protagonists' interaction with the "Orient" as more complex and less "colonizing" than that of Canetti's narrator. While Frischmuth rewrites the Bildungsroman to subvert Eurocentric assumptions underlying travel literature, Mede-Flock goes one step further by taking the focus away from the individual protagonist and intellectual life in the city, and by representing the encounter with Turkey as political. However, Turkey remains a Eurocentric construct in the two novels, and their authors, by attempting to undermine some cultural stereotypes, unwittingly reinforce others.
Keywords: Austria; Germany; relationship; Orientalism; Orient; Edward Said; gender issues; gender; criticism; Rana Kabbani; Europe' s Myths of Orient: Devise and Rule; race; class; convergence of race; Elias Canetti; Die Stimmen von Marrakesch; narrator; identification; colonizer; colonialism; colonial; representation of self; self; Barbara Frischmuth; Hanne Mede-Flock; female protagonist; colonizing; Bildungsroman; Eurocentric; travel literature; individual protagonist; intellectual life; Turkey; political; Eurocentric construct; stereotypes; undermine; reinforce